Shurah Al-Hub fii Qashidah Hub Bila Hudud lii Nizar Qabbani: Dirasah Tahliliyah Simiyaiyah - Firdaus, Muhammad; Ulfa, Fitria (Jurnal Adabiya, 2024)
This study aims to find a semiotic description of love contained in Nizar Qabbani's poem entitled "Hub Bila Hudud". In discussing these issues, this article uses Ferdinand De Sausure's semiotic theory on the concepts of signifier and signified. Signifier is a form of sound image that has meaning. Meanwhile, the signified is a form of thought/idea that explains the understanding of the signifier. This research is a library research where researchers analyze reading sources using certain theories. The results found from this study are that Nizar's poem entitled "Hub Bila Hudud" contains many words of love that refer to semiotic meanings. These results are known through Ferdinand De Sausure's semiotic theory, namely signifier (Dal) and signified (Madlul) which are used to dissect the poem "Hub Bila Hudud" by Nizar Qabbani.------------------------------------------------------------------------------------------------يهدف هذا البحث إلى إيجاد التصوير السيميائي للحب الوارد في قصيدة نزار قباني بعنوان "حب بلا حدود". في مناقشة هذه المشكلة، يستخدم الباحث النظرية السيميائية عند فرديناند دي سوسور حول مفهومي الدال والمدلول. الدال هو شكل من أشكال الصورة الصوتية التي لها معنى. والمدلول هو شكل من أشكال الفكر/الفكرة التي تشرح فهم الدال. هذا البحث هو بحث مكتبي حيث يقوم الباحث بتحليل مصادر القراءة باستخدام نظريات معينة. ومن النتائج التي يصل إليها هذا البحث أن قصيدة نزار بعنوان "حب بلا حدود" تحتوي على العديد من كلمات الحب التي تشير إلى معاني سيميائية. وتعرف هذه النتيجة من خلال النظرية السيميائية لفرديناند دي سوسير وهي الدال والمدلول.